Mejora productiva en la imprenta Kooper-5 de la empresa Procarsa mediante el uso de láminas corrugadas pre-impresas para el mercado bananero - Mina Cangá, Diego Ales (2023)
The present work is focused on improving the productivity of the Kooper-5 printing press by reducing unproductive times in which they have been lost due to excess hours in the 549 set-ups, which are 22.8 days, which represents $67,757.58 in the year 2021, in process stops 809 hours, that is, 33.7 days, which represents $99,846.78, of this time, 207 hours are directly related to the printing process, the excess hours in the set-up and the continuous stops to make adjustments, directly affect the printer performance, the proposal that is the use of pre-printed corrugated sheets, reduces by 50% the current average time that the set-up lasts and in turn eliminates stops for the printing process during productive time, this it allows you to have more time available to produce. With the implementation of the proposal, the investment can be recovered in 4 years and 3 months. The Benefit / Cost Coefficient shows us that, for the investment of each dollar, $1.13 will be received, this means that you will obtain $0.13 of benefit for the investment of each dollar, this indicates that the implementation of the proposal will be feasible for the company and convenient because it will be able to improve the productivity of the Kooper-5 printing press by 22%, going from producing 10,500 boxes/hour to 13,500 boxes/hour.